Hamman’s syndrome: spontaneous pneumomediastinum and subcutaneous emphysema during second stage of labour - Lou, Ying Yiing (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Subcutaneous emphysema with pneumomediastinum in labour is also known as Hamman’s Syndrome. Maternal pneumomediastinum associated with subcutaneous emphysema is a rare complication of pregnancy. The incidence rate being between 1:2000 and 1:10,000. Pneumomediastinum occurs most frequently in the second stage of labour in a healthy primiparous women with prolonged labour. A 29-year-old primigravida, who had no relevant medical history, had an uneventful spontaneous vaginal delivery at term. She used Entonox as analgesia in labour. She developed facial and neck oedema associated with mild breathing discomfort towards the end of her second stage. Crepitus was felt in her cheek, neck and anterior chest wall. Observations were stable including oxygen saturation. Chest X-ray demonstrated gross and extensive surgical emphysema across the chest and up into the neck and with no evidence of pneumothorax. She was managed conservatively and the subcutaneous emphysema was found to have considerably better within 24 hours. She recovered uneventfully and was discharged within 3 days of admission. A future pregnancy is planned. Hamman’s syndrome is generally a self-limiting condition. The key to successful management is early recognition followed by appropriate measures to prevent further complications in order to reduce the morbidity and mortality associated with this condition. Supportive measures alone may be the only requirement for resolution. Recurrence of the condition is rare but the appropriate management of subsequent pregnancies is unclear. Our case was appropriately managed with multidisciplinary input in the HDU on labour ward.